ANALISIS POLA PERILAKU KEUANGAN RUMAH TANGGA DALAM MENGHADAPI KENAIKAN BAHAN POKOK DI BULAN RAMADHAN - Farah Aqilah; Rayhan Aulia Pratama; Zilla Fadhia; Anza Zatira Pane; Siti Suaibah Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the pattern of household financial behavior in the face of rising prices of staples during Ramadan as well as, factors that influence the increase in prices of staples during Ramadan, and savings strategies that can be applied. This research uses a case study method with a qualitative approach to analyze the financial behavior patterns of Muslim families during Ramadan. The results of this study indicate that the increase in the price of goods during Ramadan has an impact on household spending patterns. Nevertheless, families can adapt by applying effective savings methods. The level of financial knowledge and the application of religious values play an important role in maintaining family financial stability. The adjustments made reflect strong economic adaptability. The austerity strategies taken not only demonstrate efficiency in economic management, but also highlight social values such as cooperation, shared responsibility and simplicity in spending.